Consensus-based good practice guidelines for Clinical Psychologists to support care staff in enabling sexual expression in people with intellectual disabilities - a Delphi study - English, Brad (2018)
Increasingly, society is acknowledging that people with intellectual disabilities (PWID) have sexual needs. This shift is reflected in international policy, with sexual expression acknowledged a basic human right for PWID. Staff that care for PWID have a responsibility to ensure this right is upheld. Though they generally report accepting views of PWID’s sexual expression, PWID report that their sexual expression is restricted by care staff. A lack of service-level policy regarding PWID’s sexual expression and how to support them in this, leaves care staff confused, and lacking confidence to make decisions about PWID’s care. Clinical Psychologists work with care staff who experience these difficulties. Though pockets of good practice are emerging, there is no guidance on how to best approach this work. This research sought to utilise the good practice already occurring.